SPA KAKI DIABETIK EFEKTIF MEMPERBAIKI SENSASI KAKI PADA DIABETESI - I Made Sukarja (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2018)
Chronic hyperglycemia in diabetes mellitus nonenzymatic glycosylation and excessive glucose to intracellular diffusion leads to structural abnormalities and capillary function as well as peripheral nerve injury. Nerve cell injury and supported by capillary dysfunction lead to neuropathy. Sensory neuropathy results in decreased leg sensation that is easily injured. Recovery of neuropathy is done by improving blood circulation repairing peripheral nerves. The purpose of this study was to determine the effect of diabetic foot spa on foot sensation in diabetics. The study was conducted with pre test post test with control group design on 45 people divided into 25 people into treatment group and 20 men men in the control group taken with simple random technique at Puskesmas II Denpasar Barat 2017. Treatment group given treatment in the form of diabetic foot spa covers gymnastics foot, foot soak and massage with VCO for 4 weeks, while the control group get foot exercises done by puskesmas. Foot sensation data is measured by Semmes-Weinstein monofilament. The results showed that foot spa ektof increase foot sensation in people with diabetes. It is recommended that people with diabetes can do foot spa in the form of foot exercises, soak feet and dimasase with VCO regularly.